Adaptive Event-triggered Anti-windup Compensation Control for a Class of Input Saturated Systems - LI Hong chao; DENG Hui min; LIU Jiao; JIANG Qian cheng (Journal of Harbin University of Science and Technology, 2023)
For the problem of the system performance degradation caused by input saturation, anti-windup compensator is applied to improve the performance. In order to save the network communication resources, a novel adaptive event-triggered mechanism with time-varying parameters is formulated, which can be applied to the situation where the system state cannot be measured directly. Moreover, this event-triggered mechanism can save more network communication resources compared with related event-triggered condition that has fixed parameters. A new Lyapunov function containing the rate of threshold function and exponential term is constructed, and sufficient conditions for asymptotic stability of saturated system are derived by using Lyapunov stability analysis method. An optimization problem is formulated to maximize the estimated domain of attraction for the saturated system. The minimum inter-event time interval is calculated to avoid Zeno behavior. The effectiveness of the theoretical results is verified by simulation example.